Ibrahim bin Al-Mahdi his life and succession "201 AH / 817- 9819/4203 (Journal of the College of Basic Education, 2023)
At the beginning of the year 198 AH / 814 AD, Al-Ma’mun assumed the caliphate (after the killing of the caliph Al-Amin, the impact of the conflictThe bloody one that broke out between them. Al-Ma'mun continued to reside in Marw for several years.Some believe that the reason for his stay in Marw is represented by his fear of the people of Baghdad, the supporters of Al-Amin, as well asThe role of al-Fadl ibn Sahl (; in persuading him to stay there) (©.It is noticeable that al-Ma'mun's stay outside Baghdad constituted, in fact, a clear change in the state's policyHe revealed new tendencies towards the issue of succession and centers of power and influence, which aroused the resentment of the IraqisIn general, especially the people of Baghdad, as a result of Al-Ma’mun falling under the influence of the strong influence of his minister, Al-Fadl bin Sahl A&Which led to his removal from the caliphate and the pledge of allegiance to another Abbas, Ibrahim bin Al-Mahdi, for reasons and motives that I will discuss.This research includes an introduction, two chapters and a conclusion. In the first topic, we dealt with his life. And his succession.The second topic included "political unrest in Baghdad".Then the research concluded with the most important observations that we reached, and we hope that we have succeeded in achieving thisThe goal and from God is success.